2012
DOI: 10.1088/0067-0049/198/2/12
|View full text |Cite
|
Sign up to set email alerts
|

NEUTRAL INTERSTELLAR HELIUM PARAMETERS BASED ON IBEX-Lo OBSERVATIONS AND TEST PARTICLE CALCULATIONS

Abstract: Because of its high ionization potential and weak interaction with hydrogen, Neutral Interstellar Helium is almost unaffected at the heliospheric interface with the interstellar medium and freely enters the solar system. This second most abundant species provides some of the best information on the characteristics of the interstellar gas in the Local Interstellar Cloud. The Interstellar Boundary Explorer (IBEX) is the second mission to directly detect NISHe. We present a comparison between recent IBEX NISHe ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
295
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 154 publications
(318 citation statements)
references
References 86 publications
19
295
3
1
Order By: Relevance
“…Based on measurements carried out from mid-1990s to 2001, GAS obtained a J2000 longitude λ = 255.4 • ± 0.5 • , a latitude β = 5.2 • ± 0.2 • , a speed v = 26.3 ± 0.4 km s −1 , and a temperature T = 6300 ± 340 K (Witte 2004; see also Witte et al 1996Witte et al , 2004, while IBEX found λ = 259.2 • or 259.0 • , with an uncertainty of ∼3 • , and β = 5.1 • or 4.9 • , v = 22.8 or 23.5 km s −1 , T = 6200 or 5300−9000 K by Bzowski et al (2012) and by Möbius et al (2012), respectively from measurements carried out in 2009 and 2010. The parameter values obtained from IBEX are tightly correlated with the inflow longitude, and the acceptable parameter ranges form long alleys in the parameter space.…”
Section: Motivationmentioning
confidence: 92%
See 3 more Smart Citations
“…Based on measurements carried out from mid-1990s to 2001, GAS obtained a J2000 longitude λ = 255.4 • ± 0.5 • , a latitude β = 5.2 • ± 0.2 • , a speed v = 26.3 ± 0.4 km s −1 , and a temperature T = 6300 ± 340 K (Witte 2004; see also Witte et al 1996Witte et al , 2004, while IBEX found λ = 259.2 • or 259.0 • , with an uncertainty of ∼3 • , and β = 5.1 • or 4.9 • , v = 22.8 or 23.5 km s −1 , T = 6200 or 5300−9000 K by Bzowski et al (2012) and by Möbius et al (2012), respectively from measurements carried out in 2009 and 2010. The parameter values obtained from IBEX are tightly correlated with the inflow longitude, and the acceptable parameter ranges form long alleys in the parameter space.…”
Section: Motivationmentioning
confidence: 92%
“…In addition to the data analyzed originally by Witte (2004), we process the data from the last Ulysses season in 2007, less than two years before the IBEX launch. The analysis is carried out in a similar way to the analysis presented by Bzowski et al (2012), using the same numerical code, that was adapted for the needs of GAS analysis, and the same model of He ionization A&A 569, A8 (2014) (right-hand scale) illustrates the helium photoionization rate used in this study, adopted from Bzowski et al (2013a). The two vertical bars mark the ionization rates (with uncertainties) obtained by Witte (2004) in his original analysis of the GAS observations.…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 2008, these neutrals are measured by IBEX amongst others, from which one can derive u LISM and the temperature of the interstellar neutral flow, T ISN , through the hyperbolic trajectory equation (see Bzowski et al 2012;Möbius et al 2012). The inflow vector can also be expressed by the inflow longitude, λ flow ; latitude, β flow ; and speed, V ISN .…”
Section: Contextmentioning
confidence: 99%